The Efficacy and Safety of Plant Oil Mixtures in the Treatment of Xerosis with Pruritus in Elderly People: Randomized double blind Controlled Trial - Yulia Farida Yahya; Octyvani Vani; Dimas Ega Wijaya Putra; Cyntya Sari Sovianti; Damai Trislinawati; Tiar Marina; Nur Riviati (HM Publisher, 2021)
A B S T R A C TBackground: Xerosis skin and pruritus is the most commonly found in elderly withsymptoms mild to severe recurrent pruritus, the skin looks rough, scaly, fissured orcracked caused defects in the epidermal barrier function, increase co-morbidity aschronic infections and ulcers that are difficult to heal can decrease the quality of life.Virgin Coconut Oil (VCO) has been traditionally used for people in tropical regionas a moisturizer and anti-bacterial effect. In recent study that essential plant oilmixture have effect synergistically as anti inflammatory, anti pruritus, promotingwound healing may act promoting barrier skin and therapeutic. Objective: Efficacyand safety of plant oil mixtures as therapeutic and maintenance moisturizer.forXerosis and pruritus in elderly Method:A randomized controlled trial was involved61 elderly from nursing home and geriatric clinic in Moh. Hoesin General Hospital.They were randomized into 2 groups: plant oil mixtures (n=30) and Virgin Coconutoil (VCO) (n=31), applied on the volar legs twice a day for 4 weeks.Outcomes weremeasured at baseline and weekly, week 2 and 4.To measure of clinical dry scoreused ODSS; pruritus severity and side effect used VAS; for skin hydration usedcorneometer CM825and for sebum level used sebumeter SM 810. Results:Clinicaldry score, pruritus severity of plants oil mixtures group were significantly decreasedthan VCO at week 2 and 4 (p 0.000). Skin hydration and sebum level of plants oilmixture group were significantly increased than VCO at week 2 and 4 (p0.000).Clinical dry score, pruritus severity, skin hydration, andskin sebum levels ofplant oil mixtures were significantly better than VCO at week 4 (p 0.000). There isno side effects on both of plant oil mixtures and VCO groups Conclusion: Plant oilmixtures add pureCelin oil showed better efficacy as a therapeutin and maintanancemoisturizer for xerosis and pruritus in elderly. Both of plant oil mixtures and VCOcan be tolerated and safe to use.